Here comes the body - DiRico, Maria, 1956- (DiRico, Maria. Catering hall mystery., 2020)
Mia is starting work at Belle View, her father<U+2019>s catering hall, a popular spot for weddings, office parties, and more, despite the planes that occasionally roar overhead on their way to LaGuardia and rattle the crystal chandelier. Soon she<U+2019>s planning a bachelor party for a less-than-gentlemanly groom. But it goes awry when the gigantic cake is wheeled in and a deadly surprise is revealed . . . Since some of her family<U+2019>s associates are on the shady side, the NYPD wastes no time in casting suspicion on Mia<U+2019>s father. Now, Mia<U+2019>s going to have to use all her street smarts to keep him out of Rikers Island . . .